2018
DOI: 10.1111/irv.12540
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outpatient medically attended and community‐level influenza‐like illness—New York City, 2013‐2015

Abstract: BackgroundSurveillance of influenza‐like illness (ILI) in the United States is primarily conducted through medical settings despite a significant burden of non‐medically attended ILI.ObjectivesTo assess consistency between surveillance for respiratory viruses in outpatient and community settings using ILI surveillance from the Centers for Disease Control and Prevention Influenza Incidence Surveillance Project (IISP) and the Mobile Surveillance for Acute Respiratory Infections (ARI) and Influenza‐Like Illness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Six studies [ 39 , 42 , 56 , 62 , 69 , 70 ] reported RSV laboratory testing incidence proportions in the OP setting ( Figure 4 ; Supplementary Table 5 A ). The highest RSV laboratory testing incidence proportion was observed in 2 studies with LRTI infant populations [ 42 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [ 39 , 42 , 56 , 62 , 69 , 70 ] reported RSV laboratory testing incidence proportions in the OP setting ( Figure 4 ; Supplementary Table 5 A ). The highest RSV laboratory testing incidence proportion was observed in 2 studies with LRTI infant populations [ 42 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…In future situations, health officials could consider offering testing for novel influenza virus infections free of charge at health departments or sending clinical staff to collect specimens from ill persons in their homes as a way to address some of these barriers. The latter is a strategy that has been shown to be effective in New York City for longitudinal surveillance of influenza-like illness [16,29]. In that study, home visits were conducted to obtain specimens from persons with reports of illness.…”
Section: Discussionmentioning
confidence: 99%
“…There are several ways to address these barriers, and the mechanism depends on the resources and capabilities of the state and local health care systems. In future situations where a TIM-like platform is deployed during an outbreak, health officials could consider offering testing for novel influenza virus infections free of charge at health departments or sending surveillance staff to collect specimens from ill persons in their homes; the latter is a strategy that was been shown to be effective in New York City for longitudinal surveillance of influenza-like illness [16,22]. In addition, increased education among exposed persons about the risk of novel influenza infections and the importance of detection also may increase the likelihood of testing.…”
Section: Principal Resultsmentioning
confidence: 99%